Endovascular thrombectomy: an effective and safe therapy for perioperative ischemic stroke - Feng Wang; Xiaoping Xu; Lin Zheng; Jiawei Zhong; En Wang; Yang Liu; Yang Liu; Shaofa Ke (Frontiers in Neurology)
BackgroundPerioperative ischemic stroke is a rare but devastating complication. Mechanical thrombectomy is a promising therapeutic method, but very little data is available on its efficacy and safety. This study aims to answer this question by comparing the clinical outcomes of perioperative and community-onset stroke patients after endovascular therapy.MethodsA retrospective cohort study was conducted on a total of 35 perioperative and 584 community-onset acute ischemic stroke patients who underwent endovascular thrombectomy at our hospital over the past 3.5 years. The recanalization rate, clinical recovery and cerebral hemorrhage within 90 days after therapy were compared between these two patient groups.ResultsEndovascular thrombectomy provided perioperative and community-onset ischemic stroke patients with comparable rates of successful reperfusion (mTICI ≥2b grade) (97.1% vs. 97.3%; p = 0. 967) and favorable functional recovery (mRS ≤ 2) (51.4% vs. 43.3%, p = 0.348), with no increase in severe intracranial hemorrhage (0% vs. 2.6 and 1.0%, for hematoma ≥30% of infarcted tissue and intraventricular hemorrhage, respectively) within 90 days. In addition, perioperative stroke patients had higher prevalence of atrial fibrillation (42.9% vs. 26.7%; p = 0.038) and intracranial cerebral artery stenosis without clear embolism (17.1% vs. 3.8%; p < 0.001) than community-onset stroke patients.ConclusionEndovascular thrombectomy is an effective and safe therapeutic approach for patients with perioperative ischemic stroke, although the results need to be validated by further studies with larger populations. Atrial fibrillation and large artery stenosis may contribute to the pathogenesis of perioperative ischemic stroke.